Narzędzia racjonalnego gospodarowania przestrzenią w działalności rad narodowych. Zarys rozwiązania - Trojanek, Maria (Wydział Prawa i Administracji UAM, 1986)
Presently binding legal acts tats The Protection and Forming of the Environment Act, The Peopless Councils and Territorial Self-Government System Act, The Town and Country Planning Act, create formal grounds for people's councils independent decisions in masters concerning theiir regions. This calls among others, for a different approach in cases of managing of town and country and in town and country. The article criticises the previous objective treatment of town and country, preseoting at the same time the circumstances which conditioned the said approach and its effects in the environment. A large body of the discussion is devoted to the presentation of a certain calculus approach facilitating the local authorities to: 1) follow the changes in the environmental resources resulted by adopting a certain variant of development to realization. 2) present tasks to be taken on, in order to secure a harmonious development of a given unit. The sequence of acts to be followed in that approach can be treated as one of possible tools facilitating a selection of those programs of development which would account for properties and , resources of a given area as well as for the criteria of rationality in the aspect of the society.
Instruments of rational management of land in the activity of people's councils